1999
DOI: 10.1095/biolreprod61.1.298
|View full text |Cite
|
Sign up to set email alerts
|

Production of Plasminogen Activators (PAs) in Bovine Cumulus-Oocyte Complexes during Maturation In Vitro: Effects of Epidermal Growth Factor on Production of PAs in Oocytes and Cumulus Cells1

Abstract: We examined whether plasminogen activators (PAs) are produced by bovine cumulus-oocyte complexes (COCs) during maturation in vitro. The effects of epidermal growth factor (EGF) on production of PAs in oocytes and cumulus cells were also examined. When COCs were cultured for 24 h with 30 ng/ml EGF, three plasminogen-dependent lytic zones (58.5 +/- 3.5 kDa, 79.0 +/- 3.0 kDa, and 113.5 +/- 6.5 kDa) were observed. Addition of amiloride, a competitive inhibitor of urokinase-type PA (uPA), to the zymogram eliminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…PAs and u-PAR mRNA expression, as well as PAs activity, were found to be upregulated in a spatiotemporal manner after a GnRH-induced gonadotropin surge in the bovine periovulatory follicle, indicating their significant contribution to ovulation (Dow et al, 2002). In the same study, u-PAR mRNA was found to be primarily localised in the granulosa and theca cells, 6 h after the gonadotropin surge, while in vitro maturation of denuded bovine oocytes did not result in any increase in u-PA activity, suggesting that increased u-PA might not be of oocyte origin, but is physiologically provided by cumulus cells (Park et al, 1999).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…PAs and u-PAR mRNA expression, as well as PAs activity, were found to be upregulated in a spatiotemporal manner after a GnRH-induced gonadotropin surge in the bovine periovulatory follicle, indicating their significant contribution to ovulation (Dow et al, 2002). In the same study, u-PAR mRNA was found to be primarily localised in the granulosa and theca cells, 6 h after the gonadotropin surge, while in vitro maturation of denuded bovine oocytes did not result in any increase in u-PA activity, suggesting that increased u-PA might not be of oocyte origin, but is physiologically provided by cumulus cells (Park et al, 1999).…”
mentioning
confidence: 74%
“…Nowadays, the use of somatic cells in bovine IVP has been abandoned; here, cumulus cells were solely added to facilitate the study of possible effects of u-PA on embryo development. It has been proposed that u-PA activity is physiologically provided by cumulus cells instead of oocytes (Park et al, 1999). It is therefore possible that cumulus cells might moderate u-PA activity.…”
Section: Discussionmentioning
confidence: 99%
“…Because integrin a 6 b 1 is present in the oocyte membrane and participates in human and mouse gamete fusion (36), the parallels between both models should be considered. The u-PA is synthesized by cumulus cells (37) and its activity has also been detected in in vitro matured bovine oocytes (38). Because u-PA receptors can bind integrins (39) and it has been suggested that oolemma-anchored integrins are receptors for sperm ADAM proteins, it would plausible that sperm binding to oolemma mediated by integrins triggers u-PA binding to its receptor, finally activating plasminogen.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, mRNA for PAI-1 has been also seen in the oviductal tissue (9) and plasminogen activator (PA) activity has been detected both in oviductal tissue and oviductal fluid (OF) of hamster (17). Bovine oocytes show u-PA activity (18). Mouse, rat, and Rhesus monkey oocytes show t-PA activity (12,16), and the presence of t-PA in cortical granules of rat and cow oocytes has been also proposed (19,20).…”
mentioning
confidence: 99%
“…When the urokinase activity reached a particular threshold value, the cells were again induced to secrete urokinase into the medium leading to a temporary rise in the urokinase secretion profile. Park et al (1999) reported the production of plasminogen activators from oocytes and cumulus cells and according to their findings urokinase activity in the cultured broth increased at 12 h of culture without any further increase at 24 h. A minor decline in urokinase activity in the spent medium was observed after 144 h. Similar losses of urokinase activity on prolonged maintenance of the cultures have been reported previously by Lewis (1979). Further studies are needed to be performed on inhibitor secretion by this cell line in order to have a complete understanding of the urokinase secretion profile of the cell line.…”
Section: Production Of Urokinasementioning
confidence: 99%